MiR-200c and HuR in ovarian cancer - Prislei Silvia; Martinelli Enrica; Mariani Marisa; Raspaglio Giuseppina; Sieber Steven; Ferrandina Gabriella; Shahabi Shohreh; Scambia Giovanni; Ferlini Cristiano (BMC Cancer, 2013)
Abstract Background MicroRNAs in solid malignancies can behave as predictors of either good or poor outcome. This is the case with members of the miR-200 family, which are the primary regulators of the epithelial to mesenchymal transition and have been reported to act as both oncogenes and tumor suppressors. This study assessed the role of miR-200c as regulator of class III β-tubulin (TUBB3), a factor associated with drug-resistance and poor prognosis in ovarian cancer. Methods Expression of miR-200c was assessed in a panel of ovarian cancer cell lines with inherent or acquired drug-resistance. Stable overexpression of miR-200c was obtained in A2780 and Hey cell lines. Crosslinking-coupled affinity purification method and ribonucleic-immunoprecipitation assay were used to characterise the complexes between miR-200c, HuR and 3′UTR region of TUBB3 mRNA. Nanofluidic technology and immunohistochemistry were used to analyze the expression of HuR, TUBB3 and miR-200c in 220 ovarian cancer patients. Results In a panel of ovarian adenocarcinoma cell lines, we observed a direct correlation between miR-200c expression and chemoresistance. In A2780 cells miR-200c targeted TUBB3 3′UTR, while a positive correlation was observed between miR-200c and TUBB3 expression in most of the other cell lines. Through the analysis of 3′UTR-associated complexes, we found that the miR-200c can increase the association of the RNA binding protein HuR with TUBB3 mRNA, whereas HuR binding enhanced TUBB3 mRNA translation. Most importantly, in our analysis on 220 ovarian cancer patients we observed that overexpression of miR-200c correlated with poor or good outcome depending on the cellular localization of HuR. Conclusion This study suggests a model for the combined regulatory activity of miR-200c and HuR on TUBB3 expression in ovarian cancer. When HuR is nuclear, high expression of miR-200c inhibits TUBB3 expression and results in a good prognosis, whereas when HuR occurs in cytoplasm, the same miRNA enhances TUBB3 expression and produces a poor outcome. These findings reveal the usefulness of multidimensional analysis in the investigation of the prognostic role of miRNA expression.